Phylogeny and systematics of the Sesamiaconiota Hampson species group (Lepidoptera: Noctuidae: Noctuinae: Apameini: Sesamiina) - Le Ru, Bruno; CAPDEVIELLE-DULAC, CLAIRE; Musyoka, Boaz K.; SEZONLIN, MICHEL; CONLONG, DESMOND; van den Berg, Johnnie; Cugala, DOMINGOS; Nyamukondiwa, Casper; Ong'amo, George; Clamens, Anne-Laure; J. Kergoat, Gaël (My University, 2020)
: In this study, we review six morphologically similar species of Sesamia Guenée, 1852 from Africa, including three new species that are described: Sesamia corymbosus Le Ru n. sp., S. schoenoplectus Le Ru n. sp. and S. temberma Le Ru n. sp. These six species belong to a species complex that we hereby define as the Sesamia coniota group. Host plants of four species are recorded: Schoenoplectus corymbosus (Roth ex Roem. & Schult.) J. Raynal. for S. corymbosus and S. schoenoplectus, Echinochloa pyramidalis (Lam.) Hitschc. & Chase, Eriochloa meyeriana (Nees) Pilg., Schoenoplectus corymbosus and Typha latifolia L. for S. jansei, Tams & Bowden, 1953 and Pennisetum sp. For S. temberma. We also conduct molecular phylogenetic analyses on a multimarker (four mitochondrial and two nuclear genes) molecular dataset encompassing 36 specimens (including 32 specimens belonging to the S. coniota group). Molecular analyses allow assessing the phylogenetic relationships of five out of six species of the group.
Keywords: host-plants; molecular phylogenetics; morphology; species complex; systematics; taxonomy